HUBUNGAN INDEKS MASSA TUBUH, PERSEN LEMAK TUBUH, DAN AKTIVITAS FISIK DENGAN KADAR GULA DARAH REMAJA - Naintina Lisnawati; Florentina Kusmiyati; Bagus Herwibawa; Budi Adi Kristanto; Anggit Rizkika (Journal of Nutrition College, 2023)
ABSTRACT Background: Adolescent blood sugar levels in Indonesia can be influenced by nutritional status and body composition. Adolescents with obesity and low levels of physical activity, were at risk of having high blood sugar levels. Objectives: The purpose of this study was to analyze the correlation between body mass index, percent body fat, physical activity and adolescent blood sugar levels Methods: This research was an analytic observational study with a cross sectional design. The subjects in this study were 27 students at one of the univercity in Central Java with an age range of 18-23 years who were taken by purposive sampling. Blood sugar variables were measured using instantaneous blood sugar measurements with an easy touch glucometer. Body fat percentage was measured using a Bio Impedance Analyzer (BIA). Body weight was measured using a digital scale, height was measured using a microtoise. Physical activity levels were measured using the physical activity level (PAL) recall form. Meanwhile, the data on the characteristics of the subjects were collected through a questionnaire. Data analysis used in this study was Kendall's tau-b, Mann Whitney-U and Independent Sample T-test.Results: The blood sugar levels in this study were all in the normal category. The mean blood sugar level for teenagers is 110.56 ± 21.66. Most of the body mass index (55.6%) of adolescents are included in the normal category. The majority of adolescents have a body fat percentage category of overweight as much as 37% and obesity as much as 37%. Based on the results of the analysis, it was found that there was no relationship between percent body fat, BMI, and physical activity with sugar levels.Meanwhile, there was a correlation between age and blood sugar levels (p= 0.012 r=0.380). In addition, there was a difference in the average percentage of body fat for male and female where female have more fat than male.Conclusion: Body mass index, percent body fat, and physical activity are not related to blood sugar levels. Age is another variable in this study that is related to blood sugar levels Keywords: Adolescents; Body fat percent; Blood sugar; BMI; Physical activityABSTRAK Latar belakang: Kadar gula darah remaja di Indonesia dapat dipengaruhi oleh status gizi dan komposisi tubuh. Remaja dengan status gizi obesitas berisiko memiliki kadar gula darah yang tinggi. Tingkat aktivitas fisik remaja yang rendah juga berisiko meningkatkan kadar gula darah.Tujuan: Tujuan dalam penelitian ini adalah untuk menganalisis hubungan indeks massa tubuh, persen lemak tubuh, dan aktivitas fisik dengan kadar gula darah remaja.Metode: Penelitian ini merupakan penelitian observasional analitik dengan desain cross sectional. Subjek dalam penelitian ini adalah mahasiswa di salah satu perguruan tinggi negeri di Jawa Tengah berjumlah 27 orang dengan rentang usia 18-23 tahun yang diambil secara purposive sampling. Variabel gula darah diukur menggunakan pengukuran gula darah sesaat dengan easy touch glucometer. Persen lemak tubuh diukur dengan Bio Impedance Analyzer (BIA). Berat badan diukur dengan menggunakan timbangan digital, tinggi badan diukur menggunakan microtoise. Tingkat aktivitas fisik diukur menggunakan form recall physical activity level (PAL).  Sedangkan data karakteristik subjek dikumpulkan melalui kuesioner. Analisis data yang digunakan dalam penelitian ini adalah Kendall’s tau-b, Mann Whitney U, dan Independen Sample T-test.Hasil: Kadar gula darah semaja dalam penelitian ini seluruhnya dalam kategori normal. Rerata kadar gula darah sesaat remaja adalah 110,56 ± 21,66. Sebagian besar (55,6%) indeks massa tubuh remaja termasuk dalam kategori normal. Sebagian besar remaja memiliki kategori persen lemak tubuh overweight sebanyak 37% dan obesitas sebanyak 37%. Berdasarkan hasil analisis diperoleh hasil bahwa tidak ada hubungan antara persen lemak tubuh, IMT, dan aktivitas fisik dengan kadar gula darah. Namun, ada hubungan antara usia dengan kadar gula darah (p= 0,012  r=0,380).Simpulan:  Indeks massa tubuh, persen lemak tubuh, dan aktivitas fisik tidak berhubungan dengan kadar gula darah, terdapat variabel lain dalam penelitian ini yang berhubungan dengan kadar gula darah yaitu usia.Kata Kunci : Aktivitas fisik; Gula darah; IMT; Persen lemak tubuh; Remaja